Rancang Bangun Aplikasi Pemesanan Tiket Kapal MenggunakanFramework Laravel - Fayakun Nur Rachman; Noor Alam Hadiwijaya; Tommy Bustomi (JURNAL VOKASI TEKNIK, 2025)
Information technology is one of the best solutions for solving problems in today’s fast-paced technological era and can also facilitate various types of businesses, one of which is the ticket booking service for ships and travel transportation at CV. Tiga Putra Travel. In today’s era of rapid technological development, service providers must keep up with the fast, easy, and efficient pace of modern technology. This inspired the researcher to create a website-based application for booking transportation tickets, such as ship and travel tickets. The PHP Laravel framework was chosen to build this website because Laravel has numerous libraries that simplify the process of creating a web-based application. The waterfall method was used in the web development process due to its systematic approach, ensuring the production of a quality application. In the testing phase, black box testing and alpha testing were conducted using a questionnaire with 30 respondents. The Likert scale was used to assess the functionality of the web application to ensure it is suitable for use by the general public. After conducting the questionnaire using the Likert scale, the results showed an 88% rating (very good). Based on these test results, this research produced a web-based ticket booking application that improves the efficiency of the ticket booking process at CV. Tiga Putra Travel.